Strategi Dakwah Kultural Muhammadiyah pada Ritual Adat Mappogau Hanua Masyarakat Karampuang Sinjai - UMAR UMAR (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2017)
This article examines dakwah movement and Islamic reform mission in the Karampuang, an area whose society preserve cultural heritage of Mappogau Hanua. Cultural dakwah is used by Muhammadiyah as a strategy to cope with the local culture and costumary tradition of Mappogau Hanua. This article finds that a series of customary practice of rituals of Mappogau Hanua in Karampuang society have been modified by the Muhammadiyah’s cultural dakwah movement. The Muhammadiyah dakwah strategies can be seen in three asepcts. First, participa-tive strategy and family engagement have been used to understand costumary practice of the local tradition and the way to modify it. Second, to change people’s way of thinking (mindset) in understanding Mappogau Hanua ritual, especially in conceiving the ritual practice of Mabbahang, Mappaota, Mabbaja-baja (membersihkan), Menre Ri Bulu, Mabbali Sumange’ dan Malliing. Third, educative strategy I sued by assisiting and empowering adat policy, education, religious activities, health care, and the authority of adat sustainably. Based on these three strategies of cultural dakwah, Muhammadiyah remains exist and accepted in Karampuan society.